Mechanics-based fragility assessment of existing prestressed concrete bridges under traffic loads - Parisi, Fulvio; Losanno, Daniele; Miluccio, Giacomo; Cosenza, Edoardo; ICASP14 (My University, 2023)
After catastrophic collapse of several major bridges in Italy, the safety evaluation and retrofit interventions on existing bridges became a top priority for the engineering community, road management companies and government. This promoted the publication of Italian guidelines (GL) for risk classification, structural assessment, and structural health monitoring of existing roadway bridges. In this regard, existing bridges that do not meet the performance objectives of the Italian building code (NTC) can be checked under GL-conforming traffic load models (TLMs). This study deals with a class of simply supported, beam-type, prestressed concrete bridge decks built between 1970 and 1980 in Italy. The traffic-load fragility was evaluated by implementing a Monte Carlo sampling technique to generate simplified deck models, which can be used to assess large bridge portfolios. Based on actual data, geometric and material properties, loads, and capacity model error were modelled as random variables. Fragility analysis was carried out under different TLMs provided by GL and NTC for comparative purposes. Those TLMs were combined with bridge usage limitations, such as reduced distance of external load lane from the kerb or reduced number of lanes, to support decision-making by road management companies. In the end, a European weigh-in-motion database was used to evaluate the annual failure probability of selected bridges. Analysis results show that the load pattern plays a key role in fragility estimation, underling that realistic vehicle models should be developed to achieve a target safety level conforming to current structural codes.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED